Gaya Bahasa Perumpamaan dalam Novel Cinta di dalam Gelas Karya Andrea Hirata - Agus Yulianto (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2018)
The purpose of this study is how the parable style contained in the novel Cinta Dalam Gelas and the meaning it contains. Thus the problem in this study is how the parable style contained in the novel Cinta Dalam Gelas and what the meaning it contains. This research uses descriptive qualitative method with record technic, classification and analysis. In addition, content analysis methods are also used to examine the contents of the text to know the description of the use of parable style in the novel. Based on the results of the analysis can be seen that the parable style of language used by the author includes the use of words such as, as, kind, and like.